A preliminary comparison of mastery criterion frequency values: Effects on acquisition and maintenance. (26th October 2021) - Schneider, Anna; Fienup, Daniel M.; Gussin, Rosaria; Moss, Patricia
Abstract: Higher levels of performance during skill acquisition predict higher levels of response maintenance, but less is known about how many observations of high levels of performance are needed to produce this effect of criterion levels. We analyzed two criterion‐level frequency values, or the number of observations of criterion‐level performance. We taught children with disabilities target skills to 90% accuracy observed one time or across three consecutive sessions/days. Participants required fewer sessions to meet the terminal acquisition‐performance criterion when the frequency value was set to one and response maintenance outcomes were comparable between conditions. These outcomes suggest that the frequency component of acquisition‐performance criterion is related to the efficiency of skill acquisition for participants with comparable repertoires.